Perfil clínico-epidemiológico da Hanseníase em Nossa Senhora do Socorro - Albuquerque, Manuela Andrade de (2016)
Leprosy is a chronic, infectious and systemic disease caused by the bacillus Mycobacterium leprae, which can affect both genders, at all ages, leading to physical disabilities of several degrees. It is a worldwide sanitary problem and, in Brazil, is considered as endemic. The aim of this study was describe the clinical and epidemiological profiles of the disease, investigate the risk factors associated with the cases of leprosy, as well as analyze spatially the distribution of cases in the town of Nossa Senhora do Socorro. The study is observational and case-control. We considered as cases all the individuals diagnosed with leprosy who resided in the town and who were notified in the town´s Basic Heath Units and in Aracaju´s University Hospital and Center of Medical Specialties, in 2014. As control group, we considered individuals without diagnostic of the disease and who resided in the same house or in houses on the same street as the cases. For the data collection, we used the Inquiry on Risk Factors, the SINAN`s Leprosy Investigation/Notification Forms and the method of instantaneous positioning from a point collected by GPS. There was the analysis of the clinical and epidemiological variables, and the logistics regression described the association between the exposition variables and the leprosy cases. The average age found was 48.1±19 years and individuals were mostly male, brown-skinned and had multibacillary operational classification, with predominance of the Virchowian clinical form. We found a significant association between the presence of the current cases of leprosy in the town and the presence of other diseases in the individual, with infection through leprosy. Likewise, by analyzing schooling, family average income, presence of old cases of leprosy in the town and other diseases associated, a significant influence of such variables was observed upon the appearance of leprosy cases. The location of the leprosy cases showed heterogeneous spatial distribution in the town´s urban area. Also, four important clusters were observed in the region studied: two in the north and two in the south, highlighting the Marcos Freire II region. Socioeconomic factors may be associated with the leprosy cases in the town of Nossa Senhora do Socorro.